2015
DOI: 10.1111/btp.12227
|View full text |Cite
|
Sign up to set email alerts
|

Ant Species Identity has a Greater Effect than Fire on the Outcome of an Ant Protection System inBrazilianCerrado

Abstract: Although fire‐ and ant–plant interactions influence the community structure and dynamics of Neotropical savannas, no previous studies have considered their simultaneous effects on target host plants. We monitored the effect of ant exclusion for 3 years on leaf area loss to leaf chewing insects, thrips abundance, and reproductive output of the extrafloral nectary‐bearing shrub, Peixotoa tomentosa (Malpighiaceae). We predicted that the impact of ants on herbivores and plants would depend on the ant species, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 49 publications
(96 reference statements)
7
61
0
10
Order By: Relevance
“…These species are generalist foragers that set partnerships with honeydew producers [64, 69]. The dominance of these species in Cerrado EFNs-bearing plants was also observed in other studies [2, 13, 70], and it demonstrates their strong adaptation to such environment [25]. …”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…These species are generalist foragers that set partnerships with honeydew producers [64, 69]. The dominance of these species in Cerrado EFNs-bearing plants was also observed in other studies [2, 13, 70], and it demonstrates their strong adaptation to such environment [25]. …”
Section: Discussionmentioning
confidence: 59%
“…Although many studies have demonstrated the importance of EFNs-attracted ants to plant defense against herbivores [2526], the influence of the EFN secretory activity pattern on ants remains yet not fully understood. According to O’Dowd [27], “if a primary function of foliar nectar production is the maintenance on the plant of potential anti-herbivore agents such as ants, then the deciphering of relationships among nectar production, ant visitation and leaf development is particularly important”.…”
Section: Introductionmentioning
confidence: 99%
“…torosa. The genus Crematogaster is a cosmopolitan lineage of Myrmicinae, and the majority of species nests on trees (Hölldobler & Wilson, 1990), which reduces insect herbivore attacks (Del-Claro & Marquis, 2015). However, Cr.…”
mentioning
confidence: 99%
“…Porém, o resultado da interação formiga-planta nem sempre é positivo, dependendo das espécies envolvidas, o comportamento da formiga e a estrutura da planta a ser considerada (LANGE; HANNA et al, 2015;DEL-CLARO et al, 2016). Por exemplo, em Peixotoa tomentosa (Malpighiaceae), a produção de frutos variou ao longo de três anos, fato que foi associado às espécies de formigas presentes na planta durante o período de estudo (DEL-CLARO, MARQUIS, 2015). Já em Ouratea spectabilis (Ochnaceae) a presença de formigas da espécie Cephalotes pusillus reduziu a floração da planta por seu hábito de consumir pólen (BYK; DEL-CLARO, 2010).…”
Section: Introductionunclassified